BIOCLIMATIC URBAN DESIGN – GENERAL, ECOLOGICAL AND ECONOMIC ASPECT - Stošić Mihajlović, Ljiljana; Mihajlović, Marija P; Trajković, Svetlana P (Journal of process management and new technologies, 2017)
The need for energy-efficient, bioclimatic and environmental, concept of architectural structures have caused on the one hand, a whole new scientific discipline called bioclimatic design, and on the other hand, it can be said that it is a return to the beginning or to home architecture. This paper analyzes the problem related to the general aspect of bioclimatic urban planning administered concurrently with a review of the two components and is compatible work, without which it cannot even talk about contemporary Bioclimatic urban planning and design. Specifically, these are the environmental and economic aspect, which in contemporary world and the present level of development of science and technological knowledge go together, that we cannot speak on economic approach to the problem and at the same time does not consider the impact of the observed phenomena in an ecological way, or on the environment.